Comb-Line Filter with Coupling Capacitor in Ground Plane - Toshiaki Kitamura (Active and Passive Electronic Components)
A comb-line filter with a coupling capacitor in the ground plane is proposed. The filter consists of two quarter-wavelength microstrip resonators. A coupling capacitor is inserted into the ground plane in order to build strong coupling locally along the resonators. The filtering characteristics are investigated through numerical simulations as well as experiments. Filtering characteristics that have attenuation poles at both sides of the passband are obtained. The input susceptances of even and odd modes and coupling coefficients are discussed. The filters using stepped impedance resonators (SIRs) are also discussed, and the effects of the coupling capacitor for an SIR structure are shown.